Innovations in Technologies for Fermented Food and Beverage Industries (Food Microbiology and Food Safety, 2018)
This book covers innovations in starter culture, production of health beneficial fermented food products, technological intervention in beer, wine and spirits production, marketing of alcoholic beverages, modernization of dairy plants for production of fermented dairy products, non-diary probiotics, development of automatic fermenters, and packaging technology. Furthermore, it includes genetic engineering for improved production and quality improvement of food and beverages, which allows forecasting of the quality of the final product. Specifically this includes applications of hybrid methods combining multivariate statistics and computational intelligence, the role of consumers in innovation of novel food and beverages, and IPRS in respect to food and beverages. Innovations in Technologies for Fermented Food and Beverage Industries is a resource for students, researchers, professionals in the industry, as well as governments in their efforts to adopt technologies of their interest.